Patterns of healthcare resource utilization in patients with sarcoidosis: a cross-sectional study.: Healthcare resource utilization in sarcoidosis. - Kampstra, Nynke; van der Nat, Paul B.; van Beek, Frouke T.; Grutters, Jan C.; van der Wees, Philip J. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Limited data are available on healthcare resource use and costs in patients with sarcoidosis.Objectives: The primary aim of this study was to describe cost-drivers of the top 1% and top ≥1-5% high-cost patients with sarcoidosis. The secondary aim was to compare costs of patients with and without fatigue complaints and to compare comorbidities. Methods: We conducted a retrospective observational cross-sectional study in 200 patients diagnosed with sarcoidosis. Hospital administrative databases were used to extract healthcare utilization on the individual patient level. Healthcare costs were categorized into nine groups.Results: Average total health care costs for the top 1% (n=22), top ≥1%–5% (n=88) and bottom 95% beneficiaries (n=90) were € 108.296, €53.237 and €4.817, respectively. Mean treatment time in days for the top 1%, top ≥1-5% and the random sample of the bottom 95% was 1688 days (±225), 1412 days (±367) and 775 days (±659), respectively. Mean annual costs for the top 1%, top ≥1-5% and the random sample of the bottom 95% are €51.082, €27.840 and €8.692, respectively. We identified three cost-drivers in the top 5% high-cost patients: 1) expensive medication, 2) intensive care and 3) costs made at the respiratory unit. Patients with and without fatigue showed to have comparable mean costs. High-cost patients were more likely to have multiple organs involved due to sarcoidosis.Conclusions: We identified expensive medication as the main cost-driver in the top 5% high-cost patients with sarcoidosis. The study findings can help to tailor interventions for improving the quality of care and reducing overall costs.